How to Increase Awareness in Cancer through Healthy Lifestyle Empowerment in Community - Damayanthi, Evy (Indonesian Journal of Cancer, 2009)
https://www.scribd.com/doc/45478732/How-to-Increase-Awareness-in-Cancer-through-Healthy-Lifestyle-Empowerment-in-Community